Racial and sex disparities in HIV screening outcomes within emergency departments of Harris County, Texas - Hill, Mandy J. (J Am Coll Emerg Physicians Open, 2020)
OBJECTIVES: The emergency department provides opportunities for identifying undiagnosed HIV cases. We sought to describe the racial and sex epidemiology of HIV through ED screening in Harris County, Texas, one of the most diverse and populous metropolitan cities in the Southern United States. METHODS: We used a descriptive secondary analysis of a universal HIV screening program (2010–2017) to quantify demographic differences in HIV incidence. We applied a validated codebook to a dataset by the local health department containing 894,387 records of ED visits with 62 variables to assess race/ethnicity and sex differences. RESULTS: Of 885,199 (98.9%) patients screened for HIV during an ED visit, 1795 tested positive (incidence rate = 0.2%). Of those tested for HIV, most were White (66.3%), followed by racial minorities (African Americans (29.9%), Asians (3.6%), and American Indian, Alaska Native, Native Hawaiian or Pacific Islanders (natives) (0.1%). Half of those tested were Hispanic. Conversely, of patients testing positive (n = 1782, 99.3% of positive cases), most were African American (52.6%) followed by Whites (46.6%), Asians (0.7%), and natives (0.1%). Less than half (35.5%) of positives were Hispanic. A racial disparity in HIV incidence was discovered among African American females. This group represented 16.8% of the tested population; yet accounted for 65.8% of females who tested positive for HIV and 20.3% of all HIV‐positive test results. CONCLUSION: Descriptive findings of the racial and sex epidemiology of HIV revealed that African American females had the largest disparity between the population tested and those who tested positive for HIV.